Body & soul the evolution of a tenor saxophone standard - Allen, Eric, (Eric D.) 1973-; Hawkins, Coleman 1904-1969; Young, Lester 1909-1959; Getz, Stan 1927-1991; Rollins, Sonny 1930-; Coltrane, John 1926-1967; Gordon, Dexter 1923-1990; Brecker, Michael 1949-2007; Potter, Chris 1971- (Jamey Aebersold Jazz, 2015)
Body & Soul, a song with music by Johnny Green and lyrics by Frank Eyton, Edward Heyman, and Robert Sour, was first published in 1930. It became a popular tune for jazz musicians. This volume presents transcriptions and analyses of recorded solos by Coleman Hawkins, Lester Young, Stan Getz, Sonny Rollins, John Coltrane, Dexter Gordon, Michael Brecker, and Chris Potter. With a foreword by Chris Potter
Transcriptions and analysis of solos by Coleman Hawkins, Lester Young, Stan Getz, Sonny Rollins, John Coltrane, Dexter Gordon, Michael Brecker, Chris Potter
Includes reproduction of the original 1930 sheet music cover
Keywords: Green, Johnny / 1908-1989 / Body and soul; Improvisation (Music); Jazz / Analysis, appreciation; Jazz / Interpretation (Phrasing, dynamics, etc.); Saxophone / Performance